FACTORS THAT INFLUENCE THE DECISION TO OUTSOURCE MONITORING SERVICE TO CLOUD - Gashi, Driton (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Purpose – The purpose of this thesis work is to help firms understand values that cloud based IT asset monitoring service brings and find factors that influence the decision to order cloud based monitoring service. Monitoring solutions can predict or detect a system failure and report them so that business critical IT systems are fixed on time before business is interrupted. Traditional on-premise systems continue to get harder to manage in-house because of maintenance cost and complexity. When monitoring service is migrated to cloud, it will inherit many characteristics of cloud that will be discussed in this paper. Design/methodology/approach – Articles on cloud services as well as monitoring services were reviewed. Transaction cost economics theory was used to guide this thesis work. Qualitative interviews were conducted and evaluated using thematic analysis approach. Findings – Monitoring service inherits a lot of benefits and barriers of cloud. Security concerns are however not that realistic because monitoring service does not store user confidential information. Service level agreements are risk factors because of third party infrastructure and the Internet dependencies. However, cost related benefits and technology innovations are found to be significant factors that help decision to adopt cloud base monitoring services.